2018
DOI: 10.1007/s11418-018-1221-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lawsone contents among Lawsonia inermis plant parts and neurite outgrowth accelerators from branches

Abstract: Lawsonia inermis L. (Lythraceae) is cultivated in many countries, including Japan, China, India and Egypt. Its leaves are well known as hair dye and exhibit antibacterial, anticancer, antifungal and anticonvulsant activities. However, there are few reports on its branches. 2-Hydroxy-1,4-naphthoquinone (lawsone) is a characteristic compound in its leaves. However, it remains to be clarified whether lawsone is present in other plant parts or not. In this study, we measured lawsone contents in the extracts of L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…inermis contained 2-hydroxy-1,4-naphthoquinone (lawsone). HPLC analysis showed that the extracts of Lawsonia inermis flowers, leaves and branches contained 116.9, 486.2 and 5.4 μg/g lawsone [31].…”
Section: Lawsoniamentioning
confidence: 99%
“…inermis contained 2-hydroxy-1,4-naphthoquinone (lawsone). HPLC analysis showed that the extracts of Lawsonia inermis flowers, leaves and branches contained 116.9, 486.2 and 5.4 μg/g lawsone [31].…”
Section: Lawsoniamentioning
confidence: 99%
“…Lawsone is a characteristic compound in the leaves and flowers of Lawsonia inermis L. [25]. An intermediate, 1,4-naphthoquinone can be found, for example, in black walnut leaves.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we expected that L. inermis flowers and branches could be used for health maintenance or diseases treatment with beneficial their effects without dyeing. As a beneficial effect, we reported accelerative effects on neurite outgrowth in PC12 cells [13,14].…”
mentioning
confidence: 86%
“…Dried branches of L. inermis were obtained as described in previous report [14]. A voucher of the plant is available in our laboratory [KPU-N.T.H LIB].…”
Section: Plant Materialmentioning
confidence: 99%